Binding of CCCTC-Binding Factor (CTCF) to the Minute Virus of Mice Genome Is Important for Proper Processing of Viral P4-Generated Pre-mRNAs - Boftsi, Maria (Viruses, 2020)
Specific chromatin immunoprecipitation of salt-fractionated infected cell extracts has demonstrated that the CCCTC-binding factor (CTCF), a highly conserved, 11-zinc-finger DNA-binding protein with known roles in cellular and viral genome organization and gene expression, specifically binds the genome of Minute Virus of Mice (MVM). Mutations that diminish binding of CTCF to MVM affect processing of the P4-generated pre-mRNAs. These RNAs are spliced less efficiently to generate the R1 mRNA, and definition of the NS2-specific exon upstream of the small intron is reduced, leading to relatively less R2 and the generation of a novel exon-skipped product. These results suggest a model in which CTCF is required for proper engagement of the spliceosome at the MVM small intron and for the first steps of processing of the P4-generated pre-mRNA.